DETERMINAN MANAJEMEN LABA PADA PERUSAHAAN PARIWISATA, HOTEL, DAN RESTORAN - Wahyuni, Wahyuni; Yulianto, Yocelyn; Maulidianti, Ade; Dosinta, Nina Febriana; Yunita, Khristina (Jurnal Riset Akuntansi, 2023)
Financial statements are a form of management's accountability to report users, so they are often the target of reporting engineering, such as earnings management. Managers carry out earnings management practices to show attractive financial statements to external parties of the company. Good corporate governance becomes a system that can suppress earnings management practices, including the board of directors and the audit committee. Financial performance is measured using profitability and leverage ratios to indicate earnings management practices. This study aimed to examine the effect of the board of directors, the audit committee's size, Return on Equity (ROE), and Debt Equity Ratio (DER) on earnings management. This study uses 17 tourism, restaurant, and hotel companies listed on the Indonesia Stock Exchange (IDX) during 2017-2021. The results of this study indicate that, partially, the board of directors and the audit committee does not affect earnings management. At the same time, ROE and DER negatively affect earnings management. Then, the results of this study also show that simultaneously the board of directors, audit committee, ROE and DER have a significant effect on earnings management.